PENGARUH BELANJA KESEHATAN TERHADAP ANGKA HARAPAN HIDUP KABUPATEN KOTA DI JAWA BARAT - Estro Dariatno Sihaloho (Jurusan Akuntansi Politeknik Negeri Bandung, 2019)
This paper has two objectives. The first is to estimate the effect of health expenditure on life expectancy in regencies and cities in West Java Provinces. The second is to estimate the effect of the number of poor people on life expectancy in regencies and cities in West Java Provinces. Life expectancy is a measurement of the average time of human lives. This paper uses three-technique of Data Panel regression model: Pooled OLS, Fixed Effect Model and Random Effect Model. This paper uses Data Panel on 27 Regencies and Cities in West Java Provinces from 2014 to 2016. This paper use Life expectancy as the dependent variable, health expenditure and number of poor people as the independent variable. The result shows that Pooled OLS, Fixed Effect Model and Random Effect Model estimate the health expenditure has a positive and significant effect on life expectancy in regencies and cities in West Java Provinces. Pooled OLS and Random Effect Model technique estimate number of poor people has a negative and significant effect on life expectancy in regencies and cities in West Java Provinces.